A Study on the VR Interface Design for Children Products and its Influence Towards China’s Consumerism - Yefei, Li; Naeim , Fauzi (South Asian Journal of Social Sciences and Humanities, 2024)
The present study intended to evaluate the impact of the virtual reality store interface, which comprised of two dimensions, virtual spatial cues (VR) and interactivity (INT), on Chinese customers’ purchase decisions which included the preference for product hedonic attributes (HD) and purchase intention (PIP). Secondly, the mediating role of perceived product design which encompassed aesthetics (PRAS), functionality (PFUN), and symbolism (SYMM), was investigated. A quantitative approach was implemented, combined with a survey-based strategy for data collection. The criteria for respondents included parents having children who are VR game users, and the age range of the children was between 10 to 16 years. A sample of 312 respondents was analysed with the use of statistical software. The researcher employed the prominent methodology of structural equation modelling to evaluate the proposedhypotheses. The findings demonstrated that INT positively and significantly impacts HD, whereas INT and PIN were found to have an insignificant association. VR was found to impact HD and PIN positively and significantly among virtual Chinese consumers. In terms of the mediation analysis, PRAS significantly mediated the association between INT and PIN and VR and PIN, whereas the negative mediation of PRAS in the association between INT and HD and VR and HD was not validated. Regarding the mediation effect of SYMM, it was revealed that SYMM played a significant mediating role in the four proposed associations. Lastly, the mediation effect of PFUN was found to be significant in the association between INT and HD and VR and HD, whereas PFUN was an insignificant mediator in the association between INT and PIN and VR and PIN. The study offers substantial and valuable insights into virtual consumer perception regarding product design and purchase decisions for theoretical and practical applications.
Keywords: Product design; Purchase intention; Hedonic attributes; Virtual reality